2014
DOI: 10.1021/cr4006654
|View full text |Cite
|
Sign up to set email alerts
|

Biochemistry and Theory of Proton-Coupled Electron Transfer

Abstract: havior in PCET 3400 5.3. Adiabatic and Nonadiabatic PCET Interpreted in the Context of the Schrodinger Equation and the Born−Oppenheimer (Adiabatic) Approximation 3404 5.3.1. Quantum-State Dynamics of PCET Systems and the Underlying Potential (Free) Energy Surfaces 3404 5.3.2. Investigating Coupled Electronic−Nuclear Dynamics and Deviations from the Adiabatic Approximation in PCET Systems via a Simple Model 3408 5.3.3. Formulation and Representations of Electron−Proton States 6. Extension of Marcus Theory to P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
480
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 459 publications
(491 citation statements)
references
References 462 publications
(1,553 reference statements)
8
480
0
3
Order By: Relevance
“…In the former, Brettel has demonstrated that FAD initiates oxidation of Trp382, which engages in a hole-hopping oxidation of Trp359 and finally Trp306, which deprotonates to yield the neutral tryptophan radical [1,[178][179]. For the oxidation of the terminal Trp306 found in E. coli photolyase, Schelvis and coworkers have demonstrated the electron transfer proceeds by concerted PCET below pH = 6.5, but otherwise undergoes stepwise PCET via an initial electron transfer [180].…”
Section: Indolesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the former, Brettel has demonstrated that FAD initiates oxidation of Trp382, which engages in a hole-hopping oxidation of Trp359 and finally Trp306, which deprotonates to yield the neutral tryptophan radical [1,[178][179]. For the oxidation of the terminal Trp306 found in E. coli photolyase, Schelvis and coworkers have demonstrated the electron transfer proceeds by concerted PCET below pH = 6.5, but otherwise undergoes stepwise PCET via an initial electron transfer [180].…”
Section: Indolesmentioning
confidence: 99%
“…'Proton-coupled electron transfer' (PCET) describes any elementary step (or series of elementary steps) in which both a proton and an electron are exchanged [1][2][3][4][5][6][7][8][9]. Within this broad definition, further distinctions may be drawn: if the proton and electron move simultaneously, the elementary step is referred to as a concerted PCET.…”
Section: Introductionmentioning
confidence: 99%
“…Several decades of experimental investigations (5, 7), guided by a transparent theoretical model (8), have produced a clear understanding of single-step ET in proteins. Biological electron transfers frequently are accompanied by proton transfers, introducing an additional complication (9)(10)(11). Although the details of protein structure and redox thermodynamics must be taken into account when considering individual cases (12), tunneling timetables indicate that 20-25 Å is the maximum distance that an electron (or hole, in the case of high-potential reactions) can transfer on submillisecond timescales (5,7).…”
mentioning
confidence: 99%
“…light driven | electron | proton | transfer | photoEPT P roton-coupled electron transfer (PCET) reactions, in which both electrons and protons are transferred, play an important role in redox processes in chemistry and biology with examples in water oxidation (1)(2)(3)(4), CO 2 reduction (5), mitochondrial respiration (6), and conversion of nucleotides to 2′-deoxynucleotides (7,8). Mechanistically, PCET occurs by stepwise, electron transfer followed by proton transfer(ET-PT) (9-13) or proton transfer followed by electron transfer (PT-ET), or concerted pathways (EPT) with concerted transfer in a single step.…”
mentioning
confidence: 99%